Strategic Management in Improving Company Competitiveness in Indonesia's E-commerce Industry - Harianto, Jakoep Ezra (Asian Journal of Multidisciplinary Research, 2024)
This study aims to analyze the management strategies implemented by companies in increasing competitiveness in the Indonesian e-commerce industry. By using a qualitative approach through literature study or library research, this research utilizes various sources such as scientific journals, books, industry reports, and reliable articles. The results of the analysis show that e-commerce companies in Indonesia are facing increasingly fierce competition challenges due to rapid market growth and the development of digital technology. To survive and excel, companies need to implement management strategies that focus on innovation, human resource management, technology development, and customer experience optimization. Product and service innovation strategies are one of the important keys in attracting and retaining customers. In addition, effective logistics management and the application of data-driven technologies such as artificial intelligence (AI) and big data analytics are supporting factors in improving operational efficiency. The research also finds the importance of strategic collaboration with business partners to create a competitive digital ecosystem. Based on these findings, the study recommends the application of adaptive and future-oriented approaches to ensure long-term competitiveness. This finding is expected to make a practical contribution to managers of e-commerce companies in Indonesia as well as an academic reference for further research.